Uncommon metastatic site from breast cancer - Nikolić Ivan; Ivković-Kapicl Tatjana; Kukić Biljana; Bogdanović Bogdan; Petrović Tomislav; Đan Igor; Smiljenić Dragana (Vojnosanitetski Pregled)
Introduction. Breast cancer is one of the most common malignancies in women and the main leading cause of cancer death. The most frequent sites of metastases from breast cancer are bones, lungs, the central nervous system, the liver and soft tissue. Colonic metastases from breast cancer are rare. Case report. We presented a 70-year-old woman with bulky obstructing lesion of sigmoid colon. A physician in charge on our department examined the patient and past history of breast cancer was found up. Surgery was performed with removal of sigmoid colon and three of six lymph nodes were positive. Pathological examination, including immunohistochemical stains, confirmed the diagnosis of metastatic breast cancer to sigmoid colon. The multidisciplinary oncology team suggested postoperative chemotherapy. The patient received four cycles of chemotherapy with paclitaxel followed by anastrozole. On the first control visit no disease activity was detected. Conclusion. In patients with the past history of breast cancer the symptoms of hematochezia or anemia may indicate colonic metastases.